COVID-19 Vaccine Acceptance Among Dental Professionals Based on Employment Status During the Pandemic - Zigron, Asaf; Dror, Amiel A.; Morozov, Nicole G.; Shani, Tali; Haj Khalil, Tharwat; Eisenbach, Netanel; Rayan, Doaa; Daoud, Amani; Kablan, Fares; Marei, Hesham; Sela, Eyal; Srouji, Samer (Frontiers in Medicine, 2021)
The COVID-19 pandemic spread rapidly across the globe, leading governments to impose prolonged lockdowns on both movement and commerce. Although lockdowns decrease the rates of novel infections, they can have devastating consequences on the economy and employment levels. One of the most severely affected sectors during this crisis has been dental medicine. Dental professionals are uniquely exposed to environments with high levels of occupational hazards, conferring additional risks of viral exposure and transmission. We analyzed 506 anonymous questionnaires completed by dentists and residents regarding acceptance of a future potential SARS-CoV-2 vaccine. Our results demonstrate a statistically significant correlation between the individual’s unemployment rate and their willingness to inoculate with a SARS-CoV-2 vaccine when it becomes available. This information can be used to predict trends of vaccine acceptance or rejection based on economical burden during the COVID-19 pandemic by different sectors as part of the preparedness towards global vaccination programs.